Informing employees in small and medium sized firms about training: Results of a randomized field experiment - Gerard J. Van den Berg; Christine Dauth; Pia Homrighausen; Gesine Stephan (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2020)
We mailed brochures to 10,000 randomly chosen employed German workers eligible for a subsizided occupational training program called WeGebAU,informing them about the importance of skill-upgrading occupational training in general and about WeGebAU in particular. Using survey and register data,we estimate effects of the information treatment brochure on awareness of the program, on take-up of WeGebAU and other training,and on subsequent employment. The bRochure more than doubles awareness of the program. There are no effects on WeGebAU take-up but participation in other(unsubsidized) training increasesamong employees aged below 45. Short-term labor market outcomes are not affected.
Keywords: J24; J65; 330; employment; wages; skills; randomized controlled trial; information treatment